A metodologia problematizadora da educação popular na formação em saúde da UFPB - Costa, Luana Jesus de Almeida da (2017)
Despite of the changes occurred during the last years, the curricula in the field of healthcare are still marked by the use of traditional methods, based on the verticalization of the educational process. It is evidenced that the formative process needs to be more strongly anchored in critical, reflexive, dialogical and problematizing pedagogies, which allow for more participation of the student and interaction with the social reality, among which Popular Education stands out. This study sought to investigate the presence of Popular Education problematizing method in the formation in healthcare in the Federal University of Paraiba (UFPB) and what is the perception from the students in the courses from the Health Sciences Center and the Medical Sciences Center on the use of that method. It is a descriptive, documental, observational, field and cross-sectional study, with a quantitative and qualitative character. It had as its subjects the students from the penultimate year of the undergraduate courses in healthcare from UFPB, applying a questionnaire composed of 24 questions on the aspects of healthcare formation, which was in all its steps submitted for validation (of content, semantics and statistics). Also a documental analysis was done on the Political Pedagogical Projects (PPPs) of these courses. The collected data were charted in an electronic spreadsheet in the Microsoft Office Excel 2010 software and afterwards analyzed by means of the R statistical software, on which the Factor Analysis (FA) and Cluster Analysis (CA) were applied. In the analysis of the PPPs of these courses, the presence of a dichotomy between what is defended in the PPPs and the curricular working-out was observed, as well as the perception that the students have on the formative process. Among the surveyed courses, the ones who got closer to a problematizing method were Medicine, which presents a curriculum based on the PBL, as well as Pharmaceutics and Odontology to a lesser degree. It was verified that the items 1 and 5 of the questionnaire (discussion on the subjects taught in classroom and contact with the problematizing method of Popular Education during the academic formation) exhibited significant statistic differences (p-value ≤ 0,05). In both cases, the average of the students participating in research and/or extension projects guided by PE was greater than the students who had not participated in those projects. Through the FA done on all population, it was observed that the variables of the instrument were reduced to three factors or dimensions, theoretically entitled as “teacher-student relationship”, “dialogical relationship” and “need for methodological change”. Through CA, using the dimensions generated by FA, it was perceived that in the investigated population two statistically divergent groups were present. The findings of this study emphasize that the problematizing method of Popular Education is still little evidenced in the PPP of undergraduate courses in health of the UFPB. However, the presence of the theoretical and methodological principles of the Popular Education in the perception of the evaluated students is evidenced, and it is emphasized that the extension oriented by the PE helps in this process of reorientation of the formation in health.